A preliminary survey of the histopathological features of skin from the planum nasale and adjacent skin of dogs unaffected by dermatological or respiratory disease. Issue 5 (20th July 2015) - Hutt, John H. C.; Dunn, Karen A.; Scase, Tim J.; Shipstone, Michael A.
<x xml:space="preserve">Abstract</x> Background There is a general belief that immune system cells are present in larger numbers in the planum nasale and adjacent haired skin than in other locations in the dog. However, little published information about the normal histological appearance of the skin of this area exists. Hypothesis/Objectives The aim was to obtain information about the normal histological appearance of canine skin for specific anatomical regions of the planum nasale and the haired skin adjacent to the planum nasale. Animals Samples from three sites were obtained from the planum nasale and adjacent haired skin of 25 dogs of varying age, breed and sex, with no evidence of dermatological or respiratory disease. Methods Samples were analysed to determine and quantify the immune system cells present in the samples. Slides were stained with haematoxylin and eosin or toluidine blue; immunohistochemical stains for CD3 and CD79a were applied. Results Immune system cells, including lymphocytes and plasma cells, were either very rare or present in low numbers. The majority of lymphocytes were of T‐cell origin, with only infrequent B cells identified. Samples contained numerous melanophages, consistent with pigmentary incontinence, regardless of the presence or absence of inflammatory cells. Mast cells and plasma cells were present in low numbers. Conclusions Inflammatory change noted in diagnostic biopsies from this area from dogs with clinical disease is likely to be of pathological significance. However, pigmentary incontinence appears to be common at this site in clinically normal dogs without significant inflammatory cell infiltration and is therefore not necessarily of pathological significance when seen in isolation in this location.